OP0078 The long term prognostic significance of pulmonary hypertension in sarcoidosis - a big data analysis. (15th June 2017) - Tiosano, S; Gendelman, O; Watad, A; Comaneshter, D; Cohen, A; Amital, H
Abstract : Background: Sarcoidosis is a multisystem, chronic, progressive, granulomatous disease. Sarcoidosis-associated pulmonary hypertension is well described, but not common complication of sarcoidosis 1 . In small scale studies, it has been previously described as a manifestation of advanced disease and was found to be associated with increased morbidity and mortality 2 . Previous studies have shown that treatment may be safe and improve pulmonary hemodynamics in sarcoidosis-associated pulmonary hypertension 3, 4 . However, big data analyses regarding the exact magnitude and prognosis of sarcoidosis-associated pulmonary hypertension are lacking. Objectives: To assess the long-term prognostic significance of sarcoidosis-associated pulmonary hypertension using a big data registry with a 15-year follow-up period. Methods: Utilizing the medical records of Clalit Health Services, the largest HMO in Israel, we extracted a cohort consisted of sarcoidosis patients along with their age-and-sex matched controls. Dates of registration in the medical records of sarcoidosis, pulmonary hypertension and death, as well as anthropometric information and medical comorbidities were extracted from the database. To compare the distribution of variables across the cohort strata, univariate analysis was performed using Chi-square and student t-test. Multivariate analysis using a logistic regression model was used to find variables associated with pulmonary hypertension. Survival analysis using cox proportional hazards method and log-rank test was performed to find variables associated with increased risk of all-cause mortality. Results: The cohort included 3, 993 sarcoidosis patients and 19, 856 age-and-sex matched controls. The mean age of both groups was 56, and both consisted about 63% females. Pulmonary hypertension was observed among 269 sarcoidosis patients (6.74%) vs. 400 controls (2.01%), p<0.001. In multivariate analysis, sarcoidosis was found to be independently associated with diagnosis of pulmonary hypertension (OR 3.09, 95% CI 2.6–3.67). After more than 15 years of follow-up, 710 (17.8%) of the sarcoidosis patients had died, compared to 2121 (10.7%) of the controls (p<0.001). In multivariate survival analysis, both sarcoidosis and pulmonary hypertension were found to be significantly associated with increased risk to all-cause mortality (HR 1.83, 95% CI 1.66–2.02 and HR 2.32, 95% CI 2.05–2.63, respectively). Conclusions: Sarcoidosis-associated pulmonary hypertension is associated with poor prognosis. Proper screening methods are recommended to assess whether early identification and treatment may improve life expectancy. References: Baughman, R. P., Culver, D. A. & Judson, M. A. A Concise Review of Pulmonary Sarcoidosis. Am. J. Respir. Crit. Care Med. 183, 573–581 (2011). Baughman, R. P., Engel, P. J., Taylor, L. & Lower, E. E. Survival in Sarcoidosis-Associated Pulmonary Hypertension. Chest 138, 1078–1085 (2010). Baughman, R. P. et al. Bosentan for Sarcoidosis-Associated Pulmonary Hypertension. Chest 145, 810–817 (2014). Keir, G. J. et al. Treatment of sarcoidosis-associated pulmonary hypertension: A single centre retrospective experience using targeted therapies. Sarcoidosis Vasc. Diffuse Lung Dis. 31, 82–90 (2014). Disclosure of Interest: None declared